Hidradenitis Suppurativa: Absence of Hyperhidrosis but Presence of a Proinflammatory Signature in Patients' Sweat - Verena G. Frings; Nadine Roth; Maxine Gläsel; Boris Bauer; Matthias Goebeler; Dagmar Presser; Andreas Kerstan (Medical Journals Sweden, 2022)
The role of sweat glands in hidradenitis suppurativa has been largely neglected, despite the fact that its original designation, as "hidrosadénite phlegmoneuse", implied an inflammatory malfunction of the apocrine sweat glands as the underlying pathogenic driver. The aim of this study was to evaluate the role of apocrine sweat glands with respect to the proinflammatory environment of hidradenitis suppurativa. Therefore, gravimetric assessment and multiplex cytokine assays from sweat obtained from patients with hidradenitis suppurativa along with immunofluorescence cytokine/chemokine analysis of lesional apocrine glands- bearing hidradenitis suppurativa skin were performed. Gravimetric assessment of 17 patients with hidradenitis suppurativa revealed that the condition is not associated with hyperhidrosis. However, patients seem to be more affected by subjective sweating. The current data identified a complex proinflammatory signature in hidradenitis suppurativa sweat characterized by a significant upregulation of monocyte chemoattractant protein-1, interleukin-8 (CXCL8), and interferon-γ. In agreement with this, a strong in situ expression of these mediators could be observed in apocrine glands of lesional hidradenitis suppurativa skin. These data shed new light on the proinflammatory capacity of apocrine sweat glands in hidradenitis suppurativa, which may lead to reconsideration of the role of sweat glands in hidradenitis suppurativa pathology.